Anicii Manlii Severini Boethii De divisione liber - Boethius, -524. (Philosophia Antiqua, 1998)
This volume provides the first critical edition of Boethius' De divisione . The importance of Boethius' treatise is twofold: it was widely read in the medieval schools, and it preserves the only known vestiges of Porphyry's commentary on Plato's Sophist and of Andronicus' treatise on diaeresis. The book is in four main sections: prolegomena in three parts, dealing with the date, source(s), and text of De divisione ; critical text with apparatus and English translation; detailed philological and philosophical commentary; appendix, bibliography, and word index. This is the first edition of De divisione based on the earliest extant manuscripts, and the first complete commentary in any modern language. It will be of particular interest to students of later ancient and medieval philosophy and literature.